Phosphate Inhibition of Spinach Leaf Sucrose Phosphate Synthase as Affected by Glucose-6-Phosphate and Phosphoglucoisomerase - Doehlert, Douglas C. (1984)
The inhibition patterns of inorganic phosphate (Pi) on sucrose phosphate synthase activity in the presence and absence of the allosteric activator glucose-6-P was studied, as well as the effects of phosphoglucoisomerase on fructose-6-P saturation kinetics with and without Pi. In the presence of 5 millimolar glucose-6-P, Pi was a partial competitive inhibitor with respect to both substrates, fructose-6-P and uridine diphosphate glucose. In the absence of glucose-6-P, the inhibition patterns were more complex, apparently because of the interaction of Pi at the activation site as well as the catalytic site. In addition, substrate activation by uridine diphosphate glucose was observed in the absence of effectors. The results suggested that Pi antagonizes glucose-6-P activation of sucrose phosphate synthase by competing with the activator for binding to the modifier site. The fructose-6-P saturation kinetics were hyperbolic in the absence of phosphoglucoisomerase activity, but became sigmoidal by the addition of excess phosphoglucoisomerase. The sigmoidicity persisted in the presence of Pi, but sucrose phosphate synthase activity was decreased. The apparent sigmoidal response may represent the physiological response of sucrose phosphate synthase to a change in hexose-P concentration because sucrose phosphate synthase operates in the cytosol in the presence of high activities of phosphoglucoisomerase. Thus, the enzymic production of an activator from a substrate represents a unique mechanism for generating sigmoidal enzyme kinetics.